Assessment Of The Quality Of Growth Monitoring And Promotion For Children Under Five Years At Chps Compounds In The Wassa Amenfi East District Of The Western Region - Asigri, J. (University of Ghana, 2017)
Background: Growth Monitoring and Promotion (GMP) is a preventive programme that targets the reduction of malnutrition in children in the early periods of their lives. GMP targets the caregiver and family decisions for positive child growth outcomes and has a great potential to contribute to improving child survival if well implemented. For a GMP programme to achieve its intended objective. the following conditions need to be met; proper implementation of GMP activities by skilled health workers. adequate nutrition education and counseling for care givers. and care giver understanding of information given by health care providers. Underweight rate among children under five years in the Wassa Amenfi East District remains high despite numerous logistical and technical supports by the Western Regional and the Wassa Amenfi East District Health Directorates to health facilities in the area of growth monitoring and promotion. Objective: This study assessed the quality of the growth monitoring and promotion programme administered by Community Health Nurses at Community-based Health Planning and Services (CHPS) compounds in the Wassa Amenfi East District and caregivers' satisfaction and perception of quality of the services they received under the programme. Methodology: The study was a cross sectional survey and involved both quantitative and qualitative data collection methods. A structured questionnaire was used to collect data on caregiver-child characteristics, caregiver child feeding practices, and caregivers' perception of quality of GMP. The weights of children were measured to determine their weight-for-age status. Key Informant Interviews were employed to assess the knowledge of Community Health Nurses (CHNs) on GMP and infant and young child feeding counseling and to collect data on institutional factors that affected the quality of GMP. An observation checklist developed based on the Ghana Health Service (GHS) guidelines on GMP was also used to assess the procedure of Growth Monitoring and Promotion at CHPS compounds. Multistage random sampling was used to select 8 CHPS compounds from the 8 sub-districts of the Wassa Amenfi East District. Proportionate sampling was used to determine the sample size for each CHPS compound. A total of 312 caregivers and 15 CHNs were recruited for the study. Data from caregivers were collected through exit interviews using systematic random sampling. Results: Frequent shortage of child health record booklets, insufficient CHNs at CHPS compounds, inadequate space and benches for caregivers and lack of refresher training for stafT were identified by a majority of CHNs to be the major institutional factors that atlccted their ability to render quality GMP services. Community Health Nurses at CHPS compounds had poor knowledge in GMP procedure as well as infant and young child feeding counseling. GMP procedures observed in most CHPS compounds did not conform to the GHS standards, as a result, the service was rated poor in terms of quality. Nutrition counseling otlered to caregivers was significantly associated with their child feeding practices as well as the nutritional status (weight-for-age) of their children (p<O.05) even though CHNs had poor knowledge in infant and young child feeding counseling. Conclusion: In order to improve the quality of GMP at CHPS compounds as well as improve the nutritional status of children in the Wassa Amenfi East District, there is the need for the District Health Directorate (DHD) to schedule GMP clinic days for facilities such that CHNs from other facilities and technical officers from the district health directorate can participate to support the few CHNs to provide the gamut of GMP services to caregivers.
MPH
Keywords: Growth Monitoring; Children Under Five Years; Chps Compounds; Ghana; Wassa Amenfi East District